PERAN TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN PADA TAMAN KANAK-KANAK - Alfina Lailan (Cross-border, 2020)
Various obstacles faced, of course, there are various kinds that make this happen. One of the factors that causes this to happen is educational technology. Discussing educational technology, some perceive educational technology as only a tool, which is related to facilities and infrastructure that are classified as sophisticated. But actually it is not wrong, but not perfect. Discussing educational technology is much broader than just limited to tools or facilities that are objects or goods. The method used in this study is library research. Educational technology is the application of scientific knowledge in learning so that learning objectives can be achieved effectively and efficiently, which is not only limited to tools and goods or hardware (hardware) but also software, and brainware. In the development and utilization of learning technology there are still three basic principles, namely: 1) System approach, 2) Learner-oriented, 3) Utilization of learning resources as much and varied as possible (utilizing learning resources). In the definition of learning technology it is stated that "Educational technology is theory and practice in the design, development, utilization, management, and assessment of resources and processes for learning. The results of the study illustrate that the role of educational technology in learning is very large, not only at the design level, but also at the level of development, utilization, management and assessment. The use of technology in the learning process can provide benefits both in developing aspects of child development in general as well as developing cognitive aspects specifically.